D1-dopamine receptors activate c-fos expression in the fetal suprachiasmatic nuclei. - Weaver, D R (1992)
The existence of an activatable dopamine system within the hypothalamic suprachiasmatic nuclei (SCN), the site of a biological clock, was investigated in rats during fetal life. In situ hybridization studies revealed that D1-dopamine receptor mRNA was highly expressed in the fetal SCN and not expressed in other hypothalamic regions. Cocaine injected into pregnant rats or directly into rat fetuses on day 20 of gestation selectively activated c-fos gene expression in the fetal SCN; cocaine did not induce c-fos expression elsewhere in the fetal brain or in the maternal SCN. This cocaine-induced activation of c-fos expression in fetal SCN was mediated in part through D1-dopamine receptors, as the cocaine-induced activation was partially blocked by the D1-dopamine receptor antagonist SCH 23390. In addition, the selective D1-dopamine receptor agonist SKF 38393 induced high levels of c-fos expression in the fetal SCN. The presence of an activatable dopamine system within the fetal SCN provides a mechanism through which maternal signals could entrain the fetal biological clock and through which maternally administered psychotropic drugs could alter normal development of the circadian timing system.